Detection of bacterial sulfatase activity through liquid- and solid-phase colony-based assays - Hey Young Yoon (AMB Express, 2017)
Abstract Bacterial arylsulfatases are crucial to biosynthesis in many microorganisms, as bacteria often utilize aryl sulfates as a source of sulfur. The bacterial sulfatases are associated with pathogenesis and are applied in many areas such as industry and agriculture. We developed an activity-based probe 1 for detection of bacterial sulfatase activity through liquid- and solid-phase colony-based assays. Probe 1 is hydrolyzed by sulfatase to generate fluorescent N-methyl isoindole, which is polymerized to form colored precipitates. These fluorescent and colorimetric properties of probe 1 induced upon treatment of sulfatases were successfully utilized for liquid-phase sulfatase activity assays for colonies and lysates of Klebsiella aerogenes, Mycobacterium avium and Mycobacterium smegmatis. In addition, probe 1 allowed solid-phase colony-based assays of K. aerogenes through the formation of insoluble colored precipitates, thus enabling accurate staining of target colonies under heterogeneous conditions.